Byron and the Post-Secular: Quia Impossibile. Issue 2 (December 2015) - Hopps, Gavin
Abstract : Over the last few decades, several prominent strands of criticism have encouraged us to assume that Romantic intimations of transcendence are illusions, escapist fantasies or forms of mystification. This article argues against such practices of exclusive immanence and recommends in their place a more hospitable 'post-secular' approach, which favours a non-dogmatic 'posture of perhaps'. The relevance of this alternative approach is illustrated with reference to the work of Byron, which is, I suggest, sceptical about and yet open to the possibility of religious transcendence. What's more, the article brings to light two divergent forms of openness to the religious in Byron's verse: a more reflective posture of hospitality to the paradoxical possibility of the impossible—founded on the poet's radical scepticism—and a more affective mode of openness, which discloses or disposes the poet towards that which exceeds the material.